Dynamic synthetic inertial control method of wind turbines considering fatigue load - Wang, Hanbo; Liu, Yingming; Wang, Xiaodong; Guo, Guoxian; Wang, Liming (Frontiers in Energy Research, 2023)
This paper proposes a dynamic synthetic inertia control method considering the fatigue loads of wind turbines. The control objectives include reducing the rate of change of frequency and frequency nadir of the power system and the fatigue load of the shaft and tower of the WT. A frequency regulation model of the power system containing the primary operating dynamics of WT is established. The dynamic synthetic inertia control method is proposed according to the relationship between fatigue load, wind velocity, and frequency. Case studies were conducted with a WT fatigue load under synthetic inertia control with different weights for different wind velocities and system loads. Therefore, the dynamic weights are obtained. Comparing ROCOF and FN and equivalent damage load, the efficacy of the proposed method is verified.